Improving uncertainty in Widmark equation calculations: Alcohol volume, strength and density. Issue 5 (September 2017) - Maskell, Peter D.; Alex Speers, R.; Maskell, Dawn L.
Abstract: The Widmark equation is probably the most commonly used calculation for medicolegal purposes. Recently the National Research Council (USA) and the Forensic Science Regulator (UK) have called for the uncertainty of all results to be given with all forensic measurements and calculations. To improve the uncertainty of measurement of results from Widmark calculations we have concentrated on the uncertainties of measurement involved in the calculation of amount of alcohol, that of the volume of alcohol, the concentration of alcohol and the density of alcohol as previous studies have investigated some of the other factors involved. Using experimental studies, the scientific literature and legal statutes, we have determined revised and improved uncertainties of the concentration of ethanol for Widmark calculations for both the USA and UK. Based on the calculations that we have performed we recommend the use of Monte Carlo Simulation for the determination of uncertainty of measurement for Widmark Calculations. Highlights: Widmark equation most commonly used calculation for medicolegal purposes. The results of Widmark calculations are subject to uncertainty of measurement. Revised and improved uncertainty when using ABV, drink volume and density in calculations. Monte Carlo method is recommended for uncertainty calculations.